Composition Regulation and Microstructure Characterization of Fe100-xGax Films in the Manufacturing Industry. (19th October 2021) - Shen, Zhi; Yan, Jian-Wu; Jin, Kang; Fu, Kai; Zhou, Ying-Li
Abstract : Fe100-x Gax giant magnetostrictive films (GMF) are attracting ever increasing attention for their potential application to manufacturing integrated magnetostrictive displacement sensors. However, it is difficult to fabricate Fe100-x Gax thin films with different compositions at will. The influence of compositions on alloy phases, grain sizes, film surface roughness, and magnetic domains of the films and magnetization of magnetron sputtered Fe100-x Gax films was investigated. Changing the ratio of the pure iron slice areas to alloy target areas, the desired film composition was achieved by the improved Mosaic method. The morphologies, magnetic domain structure, microstructure, and compositions of Fe100-x Gax films revealed by SEM, EDS, XRD, MFM, VSM, and TEM. The results show that there are <1 1 0 > texture in magnetron sputtered Fe100-x Gax films. The sharp peak attributed to the A2 microstructure suggests that the film is crystalline. The magnetic domain structure of Fe100-x Gax films presents a network form, and the domain width decreases with the decrease of gallium content. It is also found that the magnetic domains of the films are not uniform. The TEM result shows that there are some strip patterns in the films, and the diffraction ring is discontinuous because of the structure extinction. For a suitable candidate of microdevice applications in MEMS, the optimum composition film should be Fe83.25 Ga16.75 film.